2021
DOI: 10.1002/jmd2.12200
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of glycogen storage disease type Ib in England: A multisite survey

Abstract: Glycogen storage disease type Ib (GSDIb) is characterized by hepatomegaly and fasting hypoglycaemia as well as neutropaenia and recurrent infections. We conducted a retrospective observational study on a cohort of patients with GSDIb across England. A total of 35 patients, with a median age of 9.1 years (range 1‐39 years), were included in the study. We examined the genotype and phenotype of all patients and reported 14 novel alleles. The phenotype of GSDIb in England involves a short fasting tolerance that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, improvement clinically and in neutrophil function tests enabled us to wean and ultimately cease GCSF in all patients. Formation of a gastrostomy for enteral feeding has been contraindicated in GSD Ib patients due to poor wound healing; however, two of our patients have now successfully undergone this procedure [ 6 ]. We performed sophisticated immune response studies on 4 of our patients; however, these are expensive and not readily available and we do not feel that they add much to the clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, improvement clinically and in neutrophil function tests enabled us to wean and ultimately cease GCSF in all patients. Formation of a gastrostomy for enteral feeding has been contraindicated in GSD Ib patients due to poor wound healing; however, two of our patients have now successfully undergone this procedure [ 6 ]. We performed sophisticated immune response studies on 4 of our patients; however, these are expensive and not readily available and we do not feel that they add much to the clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…GSD Ib patients have neutropaenia and neutrophil dysfunction causing recurrent infections, periodontal inflammation and inflammatory bowel disease (IBD) [ 5 ]. The neutropaenia and neutrophil dysfunction in GSD Ib persists throughout life, and is not ameliorated by liver transplantation [ 6 9 ]. This is likely to impact on quality of life (QoL) with studies finding that patients with GSD Ib typically reported a lower QoL than patients with GSD Ia [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neutropenia and neutrophil dysfunction resulting in recurrent infections, perioral and perianal infections, and abscesses are the hallmark features of GSD Ib [ 2 ]. The administration of granulocyte colony-stimulating factor (G-CSF) improves the neutrophil count but not dysfunction and increases the risk of myelodysplasia and acute myeloid leukemia [ 1 ].…”
mentioning
confidence: 99%
“…72 A 2021 review details the current management options, burden, and unmet needs in GSD Ia, 73 providing support for clinical trials targeting GSD Ia. Findings from a retrospective, observational study on individuals with GSD Ib in England (N = 35) was published in 2021, 74 and key findings include the impact of GSD Ib on growth, fasting tolerance, bone health, as well as renal, endocrine, and gastrointestinal manifestations. That study was limited in conclusions it could draw on the natural history in adulthood due to limited adult cases (N = 7).…”
Section: Gsd Ia and Ibmentioning
confidence: 99%